Transhumanism and artificial intelligence: a transformative synergy in health and its ethical challenges - Campaña Briones, Gioconda Tatiana (2025)
This study examines convergence between transhumanism and artificial intelligence (AI) in healthcare through systematic literature review 2020-2025. Transhumanism seeks to transcend biological limitations through advanced technology, while AI facilitates precise diagnostics and personalized treatments. Four main domains were identified: AI-CRISPR personalized medicine, artificial organ bioengineering, therapeutic brain-computer interfaces, and cognitive enhancement systems. Results reveal exponential growth in clinical applications (from 25 studies in 2020 to 115 in 2025), particularly in bioengineering (40% of publications). However, critical ethical challenges emerge: algorithmic bias (25%), data privacy (22%), access equity (22%), and responsibility frameworks (15%). Successful implementation requires adaptive regulatory frameworks balancing technological innovation with fundamental human rights protection.